Pengaruh Media Audio Visual Terhadap Minat Belajar Siswa Mata Pelajaran Pendidikan Agama Islam Di SDN Mojotrisno Mojoagung Jombang - Shofwatal Qolbiyyah; Adibah Adibah; Tanjudan Sukmawinata (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2022)
This study aims to determine and describe the influence of audiovisual media on interest in learning Islamic religious education subjects at SDN Mojotrisno Mojoagung Jombang. The research method used is descriptive quantitative. Data collection techniques using questionnaires, documentation and observation. To test the hypothesis, the researcher uses quantitative data analysis with the Chi Square formula The results show that based on hypothesis testing, it can be seen that the Chi Square value of X2 is 11.385. And obtained the critical value of Chi Square at a significant level of 5% = 9,488 and at a significant level of 1% = 13,278. This proves that the calculated X2 is greater than the table X2, both at a significant level of 5% and at a significant level of 1%, namely 13,227 < 11.385 > 9.488. For the contingency coefficient (C) = 0.537 and for Cmax = 0.816 by comparing the two values ​​that appear = 0.658 when consulted into the interpretation table, the relationship between the two variables is classified as "Enough".